2003
DOI: 10.3406/refor.2003.1848
|View full text |Cite
|
Sign up to set email alerts
|

La fréquentation du tutorat : des pratiques différenciées. Enquête au sein de huit universités françaises

Abstract: Cette contribution rend compte des résultats d’une enquête par questionnaires sur le tutorat, conduite au sein de huit universités françaises. Après une description succincte des caractéristiques du public étudié, les facteurs contribuant à la fréquentation du tutorat sont analysés. Enfin, sont décrites les opinions des étudiants en matière d’utilité et de fonction des dispositifs tutoriaux. L’ensemble des résultats met en lumière une grande hétérogénéité des pratiques et des opinions au sein des différents si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 3 publications
0
2
0
6
Order By: Relevance
“…The students' respective questionnaires were also intended to understand their difficulties, to determine if and how they overcame them, to express their needs and expectations and to self-assess. As far as their content is concerned, it was relied on existing theoretical and empirical international literature about peer tutoring in higher education, adapted to the Department's context and the students' cultural background (see : Bachelet, 2010; Centre étudiant de soutien à la réussite des Services aux étudiants, 2018; Danner, Kempf & Rousvoal, 1999;Fornasieri, Lafont, Poteaux & Seré, 2003;Moussay, Étienne & Jacques Méard, 2009). In order to assure the internal validity and reliability in the research we triangulated the data from the students' questionnaires (tutors' and tutees') and the supervisor's observations.…”
Section: Data Collection and Toolsmentioning
confidence: 99%
“…The students' respective questionnaires were also intended to understand their difficulties, to determine if and how they overcame them, to express their needs and expectations and to self-assess. As far as their content is concerned, it was relied on existing theoretical and empirical international literature about peer tutoring in higher education, adapted to the Department's context and the students' cultural background (see : Bachelet, 2010; Centre étudiant de soutien à la réussite des Services aux étudiants, 2018; Danner, Kempf & Rousvoal, 1999;Fornasieri, Lafont, Poteaux & Seré, 2003;Moussay, Étienne & Jacques Méard, 2009). In order to assure the internal validity and reliability in the research we triangulated the data from the students' questionnaires (tutors' and tutees') and the supervisor's observations.…”
Section: Data Collection and Toolsmentioning
confidence: 99%
“…For example, some research has shown that the possibility of changing courses over the course of the year and the extra help given to students produce mixed results (Danner, 2000;Borras, 2011;Annoot, 2012), due to the difficulty of identifying weak students. If the consequences of rare course changes remain to be defined, research shows that methodology, tutoring and educational workshops, which are often optional, actually seldom affect the students who need it most (Danner, 2000;Fornasieri et al, 2003;Cannard et al, 2012;Ben Abid-Zarrouk & Weisser, 2013). The same conclusion can be drawn regarding new schemes to help students succeed, such as the Plan Réussite en Licence (PRL, "Success for the Bachelor's Degree"), set up in 2007.…”
Section: National Policies and Local Contextmentioning
confidence: 99%
“…Or, des recherches montrent que les possibilités de réorientations en cours d'année et l'aide apportée aux étudiants, sous la forme de tutorat notamment semblent donner des effets mitigés (Danner, 2000 ;Borras, 2011 ;Annoot, 2012), de par le ciblage difficile des étudiants fragiles. Si les effets des rares réorientations en cours d'année restent encore à déterminer, les recherches montrent que les dispositifs d'accompagnement méthodologique ou pédagogique, les plus souvent facultatifs, touchent rarement ceux qui en auraient le plus besoin (Danner, 2000 ;Fornasieri et al, 2003 ;Cannard et al, 2012 différence disparaît dès la deuxième année d'études. L'une des explications à ce résultat peut sans doute résider dans le fait que, les antennes universitaires accueillent un public relativement populaire (Pinto, 2008), pour lequel le choix de l'université, désormais proche de leur domicile, « obéit souvent à une logique de desperado : rien à perdre, tout à gagner »), puisqu'elle offre la possibilité de poursuivre à moindre coût des études dans la seule institution d'enseignement supérieur qui ne procède à aucune sélection à l'entrée (Convert, 2003).…”
Section: L'activité Salariée Des éTudiantsunclassified